DDEL-07. A PHASE I STUDY EXAMINING THE FEASIBILITY OF INTERMITTENT CONVECTION-ENHANCED DELIVERY (CED) OF MTX110 FOR THE TREATMENT OF CHILDREN WITH NEWLY DIAGNOSED DIFFUSE MIDLINE GLIOMAS. (4th December 2020) - Zacharoulis, Stergios; Szalontay, Luca; Higgins, Dominic; Englander, Zachary; Jin, ZhenZhen; Garvin, James; Zylber, Rebecca; Stark, Eileen; Maddocks, Alexis; Sethi, Chankrit; Canoll, Peter; Dammnett, Steve; et al.
Abstract: Convection-enhanced delivery (CED, the infusion of drugs under controlled pressure to the brain parenchyma via targeted micro-catheters, allows accurate anatomical targeting and delivery of higher (therapeutic) drug concentrations through clinically relevant volumes of brain tissue or tumor. Histone deacetylase inhibitors have been found in vitro to be the most active agents against Diffuse Midline Gliomas (DMGs) Using a novel device (implantable subcutaneous pump connected with catheter directly implanted into the pons/thalamus) we are performing a Phase I safety study of repeated infusions of MTX110 (MTX110, Midatech) in a dose escalation manner. Eligible patients include 3–18 years of age with newly diagnosed DMGs following radiation therapy without evidence of hemorrhage or cysts with intact organ function. Patients undergo a tumor biopsy and a single catheter (Spetzler lumbar shunt catheter, Integra, Plainsboro, NJ) is placed stereotactically into the geometric center of the tumor. A second catheter is inserted subcutaneously with the distal tubing connected to the infusion pump, (SynchroMed II (Medtronic)), also inserted subcutaneously. The infusion pump is prefilled with MTX110 and administered using wireless N'Vison Clinical programmer into two 24-hour infusions, consisting of 20 hours of drug infusions at 0.2mL/hr. The pulse is completed 7 days later. This is a dose escalation study with the infusate consisting of gadolinium and MTX110 (30, 60, or 90 microM). The study describing the first use in children of this device for direct-to-tumor drug delivery is open to recruitment (January 2020) and the preliminary data will be available for presentation by June 2020.